The dark side of liquidity regulation: Bank opacity and funding liquidity risk - Raz, Arisyi F.; McGowan, Danny; Zhao, Tianshu (Journal of Financial Intermediation, 2022)
We evaluate how the liquidity coverage rule affects US banks’ opacity and funding liquidity risk. Banks subject to the rule become significantly more opaque and funding liquidity risk increases by $245 million per quarter. Higher funding liquidity risk is more pronounced among banks that are subject to the rule’s more stringent liquidity buffers, and systemically riskier banks. Rising opacity reflects an increase in banks’ holdings of complex assets whose value is difficult to communicate to investors. The evidence highlights the unintended consequences of liquidity regulation and is consistent with theoretical models’ predictions of a trade-off between liquidity buffers and bank opacity that exacerbates funding liquidity risk.